Pengaruh Transformasi Digital Terhadap Sistem Pengendalian Manajemen Di Era Industri 4.0 - wafa virendra; Inka Mariska Zahra; Pani Aulia; Alya Fitri; Teuku Ardian Maulana (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
This study aims to analyze the influence of digital technology development on management control systems in the Industrial 4.0 era. The research method used is a descriptive qualitative approach through a literature study by reviewing various relevant scientific journals, books, and academic articles. The results of the study indicate that digitalization through the utilization of big data, artificial intelligence (AI), cloud computing, and the Internet of Things (IoT) is able to improve the effectiveness and efficiency of management control systems. Digital technology helps organizations provide real-time information, increase transparency, strengthen internal control, and support more accurate decision-making processes. However, the implementation of digitalization also faces several challenges, such as limited technological infrastructure, low human resource competencies, and data security risks. Therefore, organizations need to prepare adaptive strategies so that the implementation of digital technology can run optimally in supporting management control systems in the Industrial 4.0 era.